A Real World Report on Intravenous High-Dose and Non-High-Dose Proton-Pump Inhibitors Therapy in Patients with Endoscopically Treated High-Risk Peptic Ulcer Bleeding - Lung-Sheng Lu; Sheng-Chieh Lin; Chung-Mou Kuo; Wei-Chen Tai; Po-Lin Tseng; Kuo-Chin Chang; Chung-Huang Kuo; Seng-Kee Chuah (Gastroenterology Research and Practice)
Background and Study Aims. The optimal dose of intravenous proton-pump inhibitor (PPI) therapy for the prevention of peptic ulcer (PU) rebleeding remains controversial. This study aimed to understand the real world experiences in prescribing high-dose PPI and non-high-dose PPI for preventing rebleeding after endoscopic treatment of high-risk PU. Patients and Methods. A total of 220 subjects who received high-dose and non-high-dose pantoprazole for confirmed acute PU bleeding that were successfully treated endoscopically were enrolled. They were divided into rebleeding (n=177) and non-rebleeding groups (n=43). Randomized matching of the treatment-control group was performed. Patients were randomly selected for non-high-dose and high-dose PPI groups (n=44 in each group). Results. Univariate analysis showed, significant variables related to rebleeding were female, higher creatinine levels, and higher Rockall scores (≧6). Before case-control matching, the high-dose PPI group had higher creatinine level, higher percentage of shock at presentation, and higher Rockall scores. After randomized treatment-control matching, no statistical differences were observed for rebleeding rates between the high-dose and non-high-dose groups after case-control matching. Conclusion. This study suggests that intravenous high-dose pantoprazole may not be superior to non-high-dose regimen in reducing rebleeding in high-risk peptic ulcer bleeding after successful endoscopic therapy.